PEMANFAATAN LAHAN KOSONG MENDUKUNG KETAHANAN PANGAN LEMBANG RARU SIBUNUAN - Charlie Baka; Adewidar Marano Pata'dungan; Elkas Pasangka’ (Bajang Institute, 2025)
The Thematic Community Service Program (KKN-T) in Lembang Raru Sibunuan focused on utilizing idle land as a strategy to support food security based on local wisdom. The main problems faced by the community were low land productivity, dependence on chemical fertilizers, and limited use of household yards. The methods included observation, interviews, planning, and program implementation, such as establishing a demonstration plot with organic farming, providing tutoring for elementary students, and constructing bamboo-based trash bins. The results showed increased community awareness of land management, the benefits of organic fertilizers, and environmental care. This program strengthened collaboration between students and the community in creating a food-secure and sustainable village. In conclusion, the utilization of idle land through participatory and sustainable approaches can enhance local food security and environmental awareness..